Deutscher Soldat! Auch Dich wird die Kugel treffen! - Sowjetunion (Sowjetunion, Array (Herausgeber), 1941)
Fotomontage:
460
Keywords: Einblattdruck; Flugblatt; Weltkrieg <1939-1945>; Russlandfeldzug <1941-1945>; Gefallener; Hand <Motiv>; Propaganda; Psychologische Kriegsführung